Formal Education for Personal and Professional Development: A Case of B.Ed. Female Graduates in Pokhara - Shrestha, Roshani (Crossing the Border: International Journal of Interdisciplinary Studies, 2017)
The paper aims to prove that formal education acquired at university level has its direct relation with the personal and professional development of an individual. For instance, the female graduates of the study area have shown that they are benefitted in their professional teaching and personal life from the knowledge and skill they had acquired during their formal learning. In order to present it lucidly, the paper has been structured in six parts. The introductory part builds the context and states the research questions. It is followed by historical background, which deals with the development of formal education in Nepal; it also includes discrimination against women in education sector. The third part is theoretical discussion that deals with the impact of formal education in enhancing students’ skills and knowledge, problem solving and personality development. The fourth part is about methodology that briefly discusses the methods of data collection and analysis applied for conducting this research and drafting this article. The core part of this article is data analysis in which the collected data have been analyzed and the sixth is the conclusion followed by a list of references. Crossing the Border: International Journal of Interdisciplinary Studies Vol.5(1) 2017: 61-82